“I wanted satisfaction and I got it”: women, homicide, and capital punishment in Jim Crow Florida - Miller, Vivien (Crime, histoire & sociétés, 2023)
This article provides the first full study of capital and non-capital homicides committed by women in Florida in the interwar years and their treatment in the maturing Jim Crow criminal legal system of an active execution state. Over ninety percent of convicted female killers were African American, who were dramatically over-represented in homicide arrests and prosecutions. Unusually, two white women were sentenced to death in 1926 and 1927 in a period of political transformation, socio-economic dislocation, racial antagonism, and rising white lawbreaking. The capital conviction of an African American woman in 1929 created further unanticipated penal and clemency dilemmas for Florida governors, legal professionals, and pardon board members. The intersections of gender, race, class, violence, and punishment are explored through three main questions: Which women were accused and convicted of murder and manslaughter in Florida in the 1920s and 1930s and who were their victims? Why were these three women sentenced to death? What kinds of punishments and clemency did female killers receive? As the distinctive features of each capital murder case were often very similar to those resulting in prison terms or even acquittals, this state case study affirms that gendered capital punishment in the early twentieth century southern United States was defined largely by contingency and chance.